Roadkill on islands: where road and island ecology meet - Stamatiou, Marilena; Zotos, Savvas; Vogiatzakis, Ioannis N. (Frontiers in Conservation Science, 2025)
Human alteration of nature comes in an array of shapes and forms, with the construction and operation of road networks being a prominent and constantly expanding pressure in both geographical extent and intensity. Roads affect wildlife both directly and indirectly, with roadkill being one of the most widely researched phenomena globally in the past decade. Currently research though, mainly concerns mainland areas, with sparse information on how roads affect ecosystems on islands, which due to their isolation and size provide species with limited resources while often constitute biodiversity hotspots. In this review, we conducted a PRISMA analysis in order to source studies focused on roadkill in Small-Medium Islands (SMI), resulting in 29 studies, which we use as a basis to further discuss the topic. We highlight that research is limited, and often focused on specific species of interest (i.e. endemics), and while studies showcase a wide geographical distribution with data from islands of the Pacific, Atlantic and Indian Ocean, as well as the Mediterranean Sea, the Gulf of Mexico and the Great Australian Bight, the number of individual islands is not representative of the inhabited SMI worldwide. We also bring attention to the issue of tourism, which affects wildlife, and roadkill risks through the creation of season traffic conditions, as well as more intense construction and operation of infrastructure of all kinds. Road networks are expected to intensely expand in length in the following decades while islands are being progressively more affected by human activities despite being important biodiversity reserves. This literature review is the first step to identify the effects of road networks on islands which need to be followed by monitoring, and mitigation measures.